Africa's Pulse, April 2011 : An Analysis of Issues Shaping Africa's Economic Future - World Bank (Washington, DC, 2014)
This Africa's pulse newsletter includes the following heading: recent global economic trends and prospects; factors driving the region performance; risk to economic prospects; and rising commodity prices.